Sleep health of Australian community tennis players during the COVID-19 lockdown - Beranek, Philipp; Cruickshank, Travis; Girard, Olivier; Nosaka, Kazunori; Bartlett, Danielle; Turner, Mitchell (PeerJ, 2022)
Background Poorer sleep health outcomes have been documented in the general population during the COVID-19 outbreak. However, the impact of the COVID-19 outbreak on sleep health outcomes in specific population groups, including the sporting community, has not been extensively investigated. This study evaluated sleep health outcomes and their relationship with lifestyle behaviours during the initial COVID-19 lockdown period in Australian community tennis players. Methods This cross-sectional study evaluated sleep health outcomes and lifestyle behaviours using an online survey. The survey was disseminated online between the 24th of April and the 6th of June 2020 and comprised the Sleep Health Index, Sleep Satisfaction Tool and questions regarding weekly hours of tennis play, general physical activity, training location and alcohol consumption. Two-hundred and eighty-five individuals completed the survey. Results Compared to normative data, respondents displayed positive sleep health values during the initial COVID-19 lockdown period, with median values (IQR) of 85.3 (73.4, 91.7) and 64.8 (54.4, 73.4) for the Sleep Health Index and Sleep Satisfaction Tool, respectively. Sleep health outcomes were not significantly correlated (p > 0.05) with tennis play (Tb = 0.054–0.077), physical activity (Tb = −0.008 to 0.036), training location (Tb = −0.012 to −0.005) or alcohol consumption (Tb = −0.079 to −0.018). Conclusion Positive sleep health values were observed in Australian community-level tennis players during the initial COVID-19 pandemic. Sleep health values were not associated with lifestyle behaviours. Other unexplored factors may have influenced sleep health outcomes, including personal finances and socialisation, however these factors need to be investigated in future studies.
Keywords: Racket sport; Public health; Sleep satisfaction; Exercise; Lifestyle factor